2016
DOI: 10.1177/0363546516643812
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Ulnar Collateral Ligament Reconstruction in Major League Baseball Pitchers

Abstract: This study identified 6 key performance factors that may present significant risk factors for UCL reconstruction in MLB pitchers. These findings could help to enhance the prevention of UCL reconstruction surgery in MLB pitchers and shape the direction of future research in this domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 51 publications
1
82
0
Order By: Relevance
“…These results are intriguing and may have a large impact on predicting a pitcher’s future performance. Whiteside et al 29 demonstrated that a smaller repertoire of pitches, fewer days between games, and a greater pitch count were other factors associated with the need for future UCL reconstruction. However, the same association between pitching volume and the need for surgery was not present in predicting the need for revision UCL surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These results are intriguing and may have a large impact on predicting a pitcher’s future performance. Whiteside et al 29 demonstrated that a smaller repertoire of pitches, fewer days between games, and a greater pitch count were other factors associated with the need for future UCL reconstruction. However, the same association between pitching volume and the need for surgery was not present in predicting the need for revision UCL surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of workload and its influence on injury risk has been extensively discussed in the literature. 11,12,22,26 The relationship between parameters of workload and ROM over a baseball season has been studied in the hip in collegiate baseball players but, to our knowledge, has not been examined in the shoulder or elbow. This study did not demonstrate a correlation between innings pitched, total number of pitches thrown, or mean fastball velocity and ROM changes over a season.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of which players are likely to incur an injury has the potential of offering not only early interventions but also informed decision making for the organization before signing players to multiyear, multimillion-dollar contracts. 28 Certainly, the ethics of predicting injuries merits a discussion. The implication of assigning a player such a value runs the risk of diminishing the player's value to a franchise.…”
Section: Discussionmentioning
confidence: 99%